An Empirical Study on Nurses' Acceptance of an IoT-Based Mobile Nursing Information System in the Operating Room - Dou Huan; Mohd Rafiz Salji; Mohd Zool Hilmie Bin Mohamed Sawal (Journal of Information Systems Engineering and Business Intelligence, 2026)
Background: The continuous progress of information technology has promoted the wide application of the Internet of Things (IoT)-based mobile nursing information system (MNIS) in the medical field. These systems are particularly valuable in high-intensity environments such as operating rooms, where efficiency, accuracy of records and patient safety are essential. However, there is still a lack of empirical evidence of the use of MNIS by nursing staff in such high-risk clinical environments. Objective: This study aims to explore the acceptance of MNIS by operating room nurses and identify the key factors that affect their intention to use the system. Methods: This study adopts quantitative research methods, guided by the technology acceptance model (TAM) and information system success model (ISSM) of DeLone and McLean. The data is collected through structured questionnaires, and the measurement content includes perceived usefulness (PU), perceived ease of use (PEOU), information quality (IQ), system quality (SQ), service quality (SEQ) and willingness to use. A total of 113 valid questionnaires were collected and analyzed by statistical methods. Results: The research results show that perceived usefulness (PU), perceived ease of use (PEOU) and service quality (SEQ) have a significant positive impact on nurses' acceptance of mobile nursing information system (MNIS) (p < 0.01). Information quality (IQ) and system quality (SQ) also show moderate but less significant effects. These results support the applicability of the Technology Acceptance Model (TAM) and the Information System Service Model (ISSM) in explaining the technology acceptance in the operating room environment. Conclusion: The study confirms that perceived usefulness (PU), perceived ease of use (PEOU) and service quality (SEQ) are crucial to promote the adoption of mobile nursing information system (MNIS) for operating room nurses. These findings provide valuable guidance for hospital administrators and system developers who aim to strengthen the digital integration of clinical care. Future research should explore the long-term satisfaction, cost-effectiveness, and integration of MNIS across departments and hospital systems.   Keywords: Internet of Things (IoT), Mobile Nursing Information System (MNIS), Operating Room, Nurse Acceptance, Technology Acceptance Model (TAM), Information Systems Success Model (ISSM)